AB1191 High Prevalence of Various Upper Limb Musculoskeletal Disorders in Korean Orchardists. (9th June 2015) - Suh, Y.S.; Cheon, Y.-H.; Kim, H.-O.; Lee, W.-S.; Yoo, W.-H.; Lim, H.S.; Lee, S.-I.
Abstract : Background: Orchardists are expected to show high prevalence of upper limb musculoskeletal disorders (MSDs) due to their heavy works and working postures. However, there are no systematic studies relating upper limb MSDs in Korean orchardists. Objectives: To evaluate the prevalence and characteristics of upper limb MSDs among orchardists in rural areas of Korea. Methods: The study was carried out from June 2013 to May 2014 in a tertiary medical center. The physical examinations of upper extremities were performed by rheumatologists, orthopedists, and rehabilitation medicine specialists. The plain radiographs of shoulder, elbow, and hand, nerve conduction examination of upper extremities, and MRI of both shoulder were taken. The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire was used to assess symptoms and function of upper extremities. Results: Five hundred and fifty orchardists were included. Participants comprised of 49.5% female and 50.5% male with mean age of 59.5±8.1 years. The mean farming duration was 31.3±13.2 years. A total of 34 different types of upper limb MSDs were detected. The most frequent disorder was myofascial pain syndrome (80.5%) followed by rotator cuff syndrome (58.9%), hand osteoarthritis (58.0%), carpal tunnel syndrome (42.9%), and lateral epicondylitis (39.5%). Prevalence of any form of MSD was 98.5% and of three and more of MSDs was 77.3%. Participants with longer duration of farming had higher numbers of MSDs. Almost part of pruning and harvesting postures in orchard farming were loaded works for musculoskeletal systems. Total DASH score was relatively high (14.9±14.4). Conclusions: Almost orchardists have upper limb MSDs. Our results suggest the need to implement interventions in orchardists to prevent MSDs. References: Gomez MI, Hwang S, Stark AD, May JJ, Hallman EM, Pantea CI. An analysis of self-reported joint pain among New York farmers. J Agric Saf Health. 2003;9:143–157. Holmberg S, Stiernstrom EL, Thelin A, Svardsudd K. Musculoskeletal symptoms among farmers and non-farmers: A population based study. Int J Occup Environ Health. 2002;8:339–345. Osborne A, Blake C, Fullen BM, Meredith D, Phelan J, McNamara J, Cunningham C. Prevalence of musculoskeletal disorders among farmers: A systematic review. Am J Ind Med. 2012;55(2):143-58. Acknowledgements: This study was supported by a grant of the Center for Farmer's Safety and Health, Ministry of Agriculture, Food and Rural Affairs, Republic of Korea. Disclosure of Interest: None declared